Tool wear and surface roughness on milling carbon fibre reinforced plastic using chilled air - Muhamad Khairussaleh, Nor Khairusshima; Che Haron, Che Hassan; A. Ghani, Jaharah; Amin, A. K. M. Nurul (2012)
Carbon fibre reinforced plastic (CFRP) composite is one of expensive material which is widely used in aerospace application because of its properties. During machining, several problems arose which are due to the existence of the carbon in CFRP. Abrasive wear can be easily found on the cutting tool during machining CFRP which shorten the life of the tool and damage the surface quality. In this study the performance of solid carbide end tool and surface quality of CFRP composite during milling process was investigated at cutting speed of 160-200 m/min and feed rate of 0.025-0.05 mm/rev. It was found that the tool wear is high at higher feed rate and lower cutting speed. Longer tool life was achieved at lower feed rate and intermediate cutting speed. A good machined surface was produced at higher cutting speed and higher feed rate.